Five insights from the Global Burden of Disease Study 2019. Issue 10258 (17th October 2020) - ,; Murray, Christopher J L; Abbafati, Cristiana; Abbas, Kaja M; Abbasi, Mohammad; Abbasi-Kangevari, Mohsen; Abd-Allah, Foad; Abdollahi, Mohammad; Abedi, Parisa; Abedi, Aidin; Abolhassani, Hassan; Aboyans, Victor; et al.
Summary: The Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2019 provides a rules-based synthesis of the available evidence on levels and trends in health outcomes, a diverse set of risk factors, and health system responses. GBD 2019 covered 204 countries and territories, as well as first administrative level disaggregations for 22 countries, from 1990 to 2019. Because GBD is highly standardised and comprehensive, spanning both fatal and non-fatal outcomes, and uses a mutually exclusive and collectively exhaustive list of hierarchical disease and injury causes, the study provides a powerful basis for detailed and broad insights on global health trends and emerging challenges. GBD 2019 incorporates data from 281 586 sources and provides more than 3·5 billion estimates of health outcome and health system measures of interest for global, national, and subnational policy dialogue. All GBD estimates are publicly available and adhere to the Guidelines on Accurate and Transparent Health Estimate Reporting. From this vast amount of information, five key insights that are important for health, social, and economic development strategies have been distilled. These insights are subject to the many limitations outlined in each of the component GBD capstone papers.